The Persistent Shift in Spin-down Rate Following the Largest Crab Pulsar Glitch Rules Out External Torque Variations due to Starquakes - Xiao-Ping Zheng; Wei-Hua Wang; Chun Huang; Jian-Ping Yuan; Sheng-Jie Yuan (The Astrophysical Journal)
It was previously believed that the long-term persistent increase in the spin-down rate of the Crab pulsar following a glitch is direct evidence of a starquake-induced glitch or at least related to a starquake. Using radio data covering 1710 days following the 2017 glitch, we obtain an extreme persistent increase of the spin-down rate, which allows us to test the two prevailing models related to a starquake through an interrelation analysis between the glitch size (the amplitude of the frequency step at a glitch) and the persistent increase in the spin-down rate of the star. Our results do not support the hypothesis that glitches induce the external torque variation of the Crab pulsar, which may indicate no occurrence of a starquake during the Crab pulsar glitch. This can explain why no changes in the radio and X-ray flux, pulse profile, and spectrum of the Crab pulsar have been observed. We also suggest an internal mechanism due to superfluidity as an explanation for the long-term persistent shift in the spin-down rate of the Crab pulsar following the relatively large glitches.